Effect of trailing edge bending and sweeping on brake impeller of low-temperature turbo-expander. Issue 1 (1st May 2022) - Liang, Y W; Peng, N; Li, K R; Ke, C L; Li, J; Dong, B; Yan, H; Zhang, X H; Zheng, L W; Xiong, L Y; Liu, L Q
Abstract: With the continuous development of low-temperature turbo-expanders, the rotation speed of the rotor is getting faster. The diameter of the impeller has become one of the factors that limit the rotation speed. In this article, a new idea to improve braking capability and reduce the diameter of the brake impeller is proposed. The brake impeller of a small low-temperature air turbo-expander test bench is used as a prototype, influence of the combination of circumferential bending and sweeping at the trailing edge of the brake impeller on the braking ability is studied. It is found that the braking ability is significantly improved. To simplify the description, the combination of a forward bending of 10° and a sweeping of 20° is called combination 1. For the current brake impeller, combination 1 is the most suitable. Compared with the original impeller, the braking power of combination 1 has increased by 99.6 W, an increase of 10.4 %. Forward bending and forward sweep substantially increase the wrap angle of the brake impeller, thereby increasing the air outlet speed and improving the braking ability, but at the expense of the flow stability of the brake impeller.